A Nationwide Survey of Patient Centered Medical Home Demonstration Projects - Bitton, Asaf (Springer-Verlag, 2010)
BACKGROUND: The patient centered medical home has received considerable attention as a potential way to improve primary care quality and limit cost growth. Little information exists that systematically compares PCMH pilot projects across the country. DESIGN: Cross-sectional key-informant interviews. PARTICIPANTS: Leaders from existing PCMH demonstration projects with external payment reform. MEASUREMENTS: We used a semi-structured interview tool with the following domains: project history, organization and participants, practice requirements and selection process, medical home recognition, payment structure, practice transformation, and evaluation design. RESULTS: A total of 26 demonstrations in 18 states were interviewed. Current demonstrations include over 14,000 physicians caring for nearly 5 million patients. A majority of demonstrations are single payer, and most utilize a three component payment model (traditional fee for service, per person per month fixed payments, and bonus performance payments). The median incremental revenue per physician per year was $22,834 (range $720 to $91,146). Two major practice transformation models were identified—consultative and implementation of the chronic care model. A majority of demonstrations did not have well-developed evaluation plans. CONCLUSION: Current PCMH demonstration projects with external payment reform include large numbers of patients and physicians as well as a wide spectrum of implementation models. Key questions exist around the adequacy of current payment mechanisms and evaluation plans as public and policy interest in the PCMH model grows. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-010-1262-8) contains supplementary material, which is available to authorized users.